Drive-Thru Trash Bin - Mhd Moktar, Muhammad Fikri Hakim; Salman, Muhammad Farhan Najmi; Rizzuddin, Muhammad Adzmeen; Abdul Kadir, Muhammad Azraie; Sanik, Mohamad Erwan (Multidisciplinary Applied Research and Innovation, 2022)
Rubbish are waste material or things that are no longer wanted or needed and it is label as materials that are useless, sometimes could cause disturbance. Many people nowadays have a bad habit that can pollute the environment. The bad habits dispose of trash everywhere they go such as on the roadside. This problem effects the environment and the driver focus. Many people did not see it as a big mistake that happen because of their mind set. ‘Drive-Thru Trash Bin’ is the one of our proposal that can improve the regular trash bin and environment on the roadside. This drive- thru trash bin created to help people who in hurry on the roadside from one place to one place. This study aims to identify the need of drive-thru trash bin and propose a proper trash bin. Survey method is used to collect the information from the student about this drive-thru trash bin. As the result, the proposal design is suitable to be use and drive-thru trash bin is needed at ‘Kolej Kediaman UTHM Pagoh’.